ANALYSIS OF SOFTWARE TOOLS FOR ADAPTATION AND PRODUCTIVITY ENHANCEMENT OF HUMAN CAPITAL IN THE AGRO-SECTOR - PRYSHLIAK, Kateryna; SEMENENKO, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The modern agricultural sector is constantly evolving under the influence of digital technologies, which open new opportunities for improving human capital management efficiency. This article explores the role of software tools in the adaptation process of new employees in the agro-sector and in enhancing their productivity. Significant attention is given to the analysis of digital solutions used for personnel management, training, and performance assessment in the agricultural sector in Ukraine and abroad. The article examines key trends in the digitalization of agribusiness, including the use of human resource management systems (HRM), learning management systems (LMS), VR/AR simulations, mobile applications for microlearning, and analytical tools for employee performance monitoring. The integration of such technologies helps reduce the adaptation time for new employees, lower training costs, and improve the productivity of agricultural enterprises. An analysis of the Ukrainian market has shown that the implementation of digital HR solutions is constrained by several factors, including insufficient funding, a lack of digital literacy among employees, and weak integration with other business processes. However, the growing interest in automating human capital management creates prerequisites for further development in this area. The European experience demonstrates a high level of integration of modern HRM systems, active use of AI technologies for personalized learning, and automation of personnel management processes. In the United States, a wide range of digital learning tools is observed, along with the application of big data for productivity assessment and the implementation of platforms for developing soft skills among agro-sector employees. A comparative analysis of the effectiveness of various software solutions was conducted based on criteria such as ease of implementation, financial affordability, integration with other systems, and impact on workforce productivity. The study found that the most effective models combine the automation of routine tasks, flexible learning opportunities, and analytical mechanisms for assessing employee progress. The article also explores the prospects for the development of digital solutions for human capital management in Ukraine’s agro-sector, including the adaptation of European and American experiences. Recommendations are proposed for the implementation of VR/AR-based training, mobile platforms for continuous professional development, and expanding state support for digital HR tools in the agricultural sector. Digital HR solutions are a key factor in improving employee productivity in the agro-sector and ensuring their swift adaptation to modern working conditions. The use of software tools in personnel management contributes to workflow optimization, increased employee efficiency, and the competitiveness of agricultural enterprises in the context of global digital transformation.